2019
DOI: 10.3126/mjsbh.v18i2.24089
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maximum Phonation Duration and S/Z Ratio in Individuals with Asthma, Tuberculosis and Clinically Normal Voice

Abstract: Introduction: The ability of a person to phonate a sound gets affected in different laryngeal and respiratory pathology which can be measured by the help of two measure called as Maximum Phonation Duration (MPD) and S/Z ratio that  helps to assess the efficiency of  respiratory and phonatory system. The aim of this study is to measure the MPD and S/Z ratio in Normal, Tuberculosis and Asthma group patient. Methods: The participant included Normal, Asthma and Tuberculosis patient where the recording was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The effect of an impaired power source has previously been studied using S/Z ratio on patients with asthma, COPD, and COVID-19. 23,24,35,36 Two studies reported no significant differences for S/Z ratio between controls and asthma or COVID-19 patients regardless of severity. 24,35 Two other studies reported significantly greater S/Z ratios between asthma and COPD patients and controls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The effect of an impaired power source has previously been studied using S/Z ratio on patients with asthma, COPD, and COVID-19. 23,24,35,36 Two studies reported no significant differences for S/Z ratio between controls and asthma or COVID-19 patients regardless of severity. 24,35 Two other studies reported significantly greater S/Z ratios between asthma and COPD patients and controls.…”
Section: Discussionmentioning
confidence: 98%
“…23,24,35,36 Two studies reported no significant differences for S/Z ratio between controls and asthma or COVID-19 patients regardless of severity. 24,35 Two other studies reported significantly greater S/Z ratios between asthma and COPD patients and controls. 23,36 This study found a significant difference in airflow based on assumed impaired power source with a small effect size.…”
Section: Discussionmentioning
confidence: 98%